RITUAL MAâATENU SEBAGAI MEDIA KONSTRUKSI IDENTITAS KOMUNITAS MUSLIM HATUHAHA DI PELAUW MALUKU TENGAH - Rumahuru, Yance Z. (Jurnal Kawistara, 2012)
This article aims to expalin identity construction of the Hatuhaha muslim community in Pelauw territory,one which use ritual as its main arena. Data on maâatenu ritual was collected through of maâatenuimplementation, and interviewing of informants in Pelauw.There are ritual partisans and ritual leaderswho use symbols in the ritual. The article relates the present ritual to their historical evens and the currentcondition of local community. This research concludes that (1) the ritual has been a useful and strategicmedia for identity construction, and (2) through the ritual implementationof ritual, the interpersonalolidarity of Pelauw poeple or Hatuhaha muslim community has been well-developed, it is knoum locallythe maningkamu relation.